NEW HORIZONS OF EDUCATION: SHARPENING DIGITAL INTELLIGENCE FOR TODAY'S COMPETENCIES - Haryanto Haryanto; Moh. Imron Rosidi; Jefri Rieski Triyanto (Adisam Publisher, 2025)
Digital intelligence is a key element in modern education that explores how determination, skills, and ethics in using technology can be enhanced-integral to improving students' digital competence. The research method in this study uses literature by searching for literature that fits the context of the study. The results show that digital intelligence is not simply about mastering technological tools, but includes informatics skills, media knowledge, ethics and online social competence. The results highlight the importance of a holistic approach to education that refers to the creative, critical and responsible use of technology. This includes flexible and integrated curriculum implementation, effective teacher training and fostering a school climate that supports digital learning.